Effect of N-95 Mask on Oxygen Saturation Level in Health Care Workers and Their Experience While Using N-95 Mask - Sinha, Devika; Bhandary, Satheesh Kumar; Aroor, Rajeshwary; Reddy, Rashmitha; Alva, Shravan (Journal of Health and Allied Sciences NU, 2021)
Background N-95 masks are in high demand during this COVID-19 pandemic but wearing an N-95 mask is a real challenge to the health workers during their duty hours. The present study aims to measure the effect of the N-95 mask on oxygen saturation level in the blood and the discomforts experienced while using it.Materials and Methods Oxygen saturation was measured in 80 health care workers before and after wearing the N-95 mask continuously for more than 6 hours. The participants were asked to fill a questionnaire regarding various discomforts of N-95 mask usage, which consisted of 14 questions.Results The most common discomfort was pain around the pinna followed by difficulty in breathing and fogging of spectacles or goggles. In addition, 71% of them had decreased oxygen saturation by 1%.Conclusion N-95 mask can alter the oxygen saturation but it does not produce significant effects in healthy individuals. It can significantly affect patients with compromised airways.
Keywords: N-95 mask; health care workers; oxygen saturation; SpO2; COVID-19; discomfort